Effects of patterned electrical sensory nerve stimulation and static stretching on joint range of motion and passive torque - Saito, Akira; Mizuno, Takamasa (Frontiers in Neuroscience, 2023)
Static stretching and proprioceptive neuromuscular facilitation stretching techniques can modulate specific neural mechanisms to improve range of motion. However, the effects of modulation of these neural pathways on changes in the range of motion with static stretching remain unclear.Patterned electrical stimulation of the sensory nerve induces plastic changes in reciprocal Ia inhibition. The present study examined the effects of patterned electrical stimulation and static stretching on range of motion and passive torque in plantarflexion muscles. The subjects were 14 young men (age 20.8 ± 1.3 years). The effects of patterned electrical stimulation (10 pulses at 100 Hz every 1.5 s) or uniform electrical stimulation (one pulse every 150 msec) to the common peroneal nerve for 20 min on reciprocal Ia inhibition of the Hoffman-reflex (H-reflex) were examined. Reciprocal Ia inhibition was evaluated as short-latency suppression of the soleus Hreflex by conditioning stimulation of the common peroneal nerve. Then, the effects of transcutaneous electrical nerve stimulation (patterned electrical stimulation or uniform electrical stimulation) or prolonged resting (without electrical stimulation) and static 3-min stretching on the maximal dorsiflexion angle and passive torque were investigated. The passive ankle dorsiflexion test was performed on an isokinetic dynamometer. Stretch tolerance and stiffness of the muscletendon unit were evaluated by the peak and slope of passive torques, respectively. Patterned electrical stimulation significantly increased reciprocal Ia inhibition of soleus H-reflex amplitude (9.7 ± 6.1%), but uniform electrical stimulation decreased it significantly (19.5 ± 8.8%). The maximal dorsiflexion angle was significantly changed by patterned electrical stimulation (4.0 ± 1.4°), uniform electrical stimulation (3.8 ± 2.3°), and stretching without electrical stimulation (2.1 ± 3.3°). The increase of stretch tolerance was significantly greater after patterned electrical stimulation and uniform electrical stimulation than after stretching without electrical stimulation.Stiffness of the muscle-tendon unit was significantly decreased by patterned electrical stimulation, uniform electrical stimulation, and stretching without electrical stimulation. Transcutaneous electrical nerve stimulation and static stretching improve stretch tolerance regardless of the degree of reciprocal Ia inhibition.